2020
DOI: 10.1002/ehf2.12640
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and B‐lines on lung ultrasonography in chronic and acute heart failure

Abstract: Aims Increased body mass index (BMI) is common in heart failure (HF) patients and is associated with lower levels of Nterminal pro-brain natriuretic peptide (NT-proBNP). We evaluated the influence of BMI on lung ultrasonography (LUS) findings indicative of pulmonary congestion (i.e. B-lines) in patients with chronic and acute HF (AHF). Methods and resultsWe analysed ambulatory chronic HF (n = 118) and hospitalized AHF (n = 177) patients (mean age 70 years, 64% men, mean BMI 29 kg/m 2 , mean ejection fraction 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
(33 reference statements)
1
9
0
8
Order By: Relevance
“…The accuracy of lung POCUS may be impacted by patient factors. Elevated BMI reduced the sensitivity of lung POCUS for COVID-19, consistent with prior studies that have reported similar effects of obesity [ 33 ]. Pre-existing interstitial lung disease reduced the specificity of lung POCUS for COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…The accuracy of lung POCUS may be impacted by patient factors. Elevated BMI reduced the sensitivity of lung POCUS for COVID-19, consistent with prior studies that have reported similar effects of obesity [ 33 ]. Pre-existing interstitial lung disease reduced the specificity of lung POCUS for COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…Our observation is different from the findings of Palazzuoli et al They found that in patients admitted to due to heart failure, the number of USBLs was lower in obese patients. An inverse correlation of USBLs and BMI was observed [33,34]. The interrelation between obesity and the severity of lung congestion deserves more attention.…”
Section: Discussionmentioning
confidence: 89%
“…B-lines are discrete count variables and we used unadjusted and adjusted negative binomial regression models (NBR) to explore associations between the total sum of B-lines and variables known to be associated with B-lines: Age, BMI, diuretics before LUS, congestion on CXR and infiltrate on CXR. [17][18][19][20][21] Results from the NBR models are reported as ratios with…”
Section: Discussionmentioning
confidence: 99%
“…B-lines are discrete count variables and we used unadjusted and adjusted negative binomial regression models (NBR) to explore associations between the total sum of B-lines and variables known to be associated with B-lines: Age, BMI, diuretics before LUS, congestion on CXR and infiltrate on CXR. 17-21 Results from the NBR models are reported as ratios with 95% confidence intervals (CI) and represent % increase or decrease in B-lines. Dynamic change in B-lines between consecutive LUS were assessed with the Wilcoxon signed rank test.…”
Section: Methodsmentioning
confidence: 99%